Performance-based design in emergency evacuation: From maneuver to simulation in school design. (January 2021) - Rostami, Reza; Alaghmandan, Matin
Abstract: One of the most critical issues in every country's Buildings National Regulations is a fast and convenient building evacuation on fire and emergency. Educational spaces beside stadiums, subway stations, and tall buildings are supposed among the most accumulative and crowded public areas. Holding maneuvers, monitoring the evacuation process, and extracting the probability distribution functions of operations, we can simulate the evacuation and be hopeful of analyzing the process successfully. In this article, at first, observations and precise details of the held maneuver in an elementary school besides pathological points on students' behavior on building evacuation are given. We introduce the extracted distribution functions; after that, based on these distribution functions and thanks to the Pathfinder simulator, we simulate the maneuver. Finally, we investigate the impact of parameters like stairs wide, landing depth, and even form of stairs on evacuation time. It is evident that because of user's congruency in all elementary schools, using the data produced in this research, it is possible to analyze the evacuation process in every other elementary school, even those that are unbuilt. Highlights: Extracting probability distribution function of evacuation in an elementary school. Computational Simulation for evacuation in the selected school. Evacuation optimization on the selected school. Considering the effect of parameters like stairs wide, landing, etc. on evacuation.